Endobronchial brachytherapy with curative intent: the impact of reference points setting according to the bronchial diameter. (1st July 2017) - Nomoto, Yoshihito; Ii, Noriko; Murashima, Shuichi; Yamashita, Yasufumi; Ochiai, Satoru; Takada, Akinori; Toyomasu, Yutaka; Kawamura, Tomoko; Sakuma, Hajime
Abstract: Endobronchial brachytherapy (EBB) is an effective treatment for endobronchial tumors. However, bronchial toxicity caused by over-irradiation remains problematic. To decrease bronchial toxicity, we developed a source-centralizing applicator for EBB. The purpose of the present study was to assess the efficacy and safety of EBB with varying reference dose points according to the bronchial diameter, using a source-centralizing applicator. We reviewed 15 patients with endobronchial carcinoma who were treated with curative intent using a combination of external beam radiotherapy (EBRT) and high-dose-rate EBB between 2005 and 2014. During each EBB session, we used a source-centralizing applicator that maintained the source-delivering catheter in the center of the bronchial lumen. Reference dose points were 5–7 mm from the source axis, depending on the bronchial diameter. The median radiation doses of EBRT and EBB were 40 Gy in 20 fractions and 18 Gy in 3 fractions, respectively. The median observation period was 36 months. The 3-year overall survival, progression-free survival and local control rates were 79%, 77% and 100%, respectively. Grade 2 radiation pneumonitis was observed in two cases. Bronchial toxicities, such as hemoptysis or the symptoms of chronic bronchitis, were not observed. EBB with varying reference dose points according to bronchial diameter, using a source-centralizing applicator, is a promising procedure that may be effective for tumor elimination and reducing toxicity to the bronchial wall.